2015
DOI: 10.15838/esc/2015.3.39.11
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Level of Happiness: a Review of Russian and Foreign Research

Abstract: Аннотация. В статье представлены основные результаты первого этапа исследования субъективной удовлетворенности качеством жизни и ее влияния на социальное развитие, начатого научным коллективом ИСЭРТ РАН в 2015 г. Показано, что субъективная оценка качества жизни является критерием оценки эффективности государственного управления, индикатором восприятия населением экономических, социальных и политических решений. На базе обобщения отечественного и международного опыта обоснована значимость в постиндустриальной э… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 4 publications
0
5
0
1
Order By: Relevance
“…There is a growing interest in the study of the subjective phenomenon of happiness [1] in the world. The tendency of modern science is a desire for a quantitative expression of the studied society characteristics and a simultaneous appeal to those sides of life that the exact quantitative analysis traditionally ignores [1]. Happiness is one of these society characteristics [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a growing interest in the study of the subjective phenomenon of happiness [1] in the world. The tendency of modern science is a desire for a quantitative expression of the studied society characteristics and a simultaneous appeal to those sides of life that the exact quantitative analysis traditionally ignores [1]. Happiness is one of these society characteristics [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…The tendency of modern science is a desire for a quantitative expression of the studied society characteristics and a simultaneous appeal to those sides of life that the exact quantitative analysis traditionally ignores [1]. Happiness is one of these society characteristics [1,2]. For the first time in Bhutan, it was suggested that the Happiness Index, rather than GDP, be given greater importance [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Замена ВВП категорией «валового национального счастья» (Gross National Happiness) впервые была предпринята в Бутане и подразумевала измерение качества жизни в балансе между материальным и духовным. Само это понятие было введено еще в 1972 году королем Бутана Джигме Сингье Вангчуком [9] (Shmatova, Morev, 2015). Бутан является единственной страной, которая приняла валовое национальное счастье вместо ВВП в качестве основного показателя развития.…”
Section: субъективные показатели благосостоянияunclassified
“…For the first time in Bhutan, it has been proposed to give more importance to the Happiness Index rather than GDP [8]. In modern science, when assessing happiness, there is a desire to combine a quantitative analysis of the characteristics of society with a traditionally inaccurate analysis [9]. The happiness index is calculated according to several parameters (GDP, life expectancy, ecology, life satisfaction and many others [10].…”
Section: Introductionmentioning
confidence: 99%